Consideration of various configurations of SG6043-based rotor applied in small capacity horizontal axis wind turbine - Dinh Van, Thin; Nguyen Huu, Duc; Le Quang, Sang (International Journal of Renewable Energy Development, 2024)
The SG6043 airfoil model is well known for its high aerodynamic efficiency and it is suitable for designing small wind turbine blades. This paper determined the optimal blade configurations using only the SG6043 airfoil model with ten different lengths from 1 m to 10 m. Then, it proposed the most suitable model for a rated wind speed of 5 m/s in Vietnam. The chord and twist values of each blade’s part were optimized by using the Betz optimization method (BOM) in the Qblade open software. Several important characteristic quantities such as lift coefficient (Cl), drag coefficient (Cd), power factor (Cp) and power (P) of the different blade configurations are determined by using a combination of both XFLR5 code and Qblade software. After that, parameters related to operation such as pitch angle and rotation speed of the rotor were also investigated to find the operating conditions for the best efficiency of wind energy exploitation. The obtained results show that the Cp of the blades has a maximum value of about 0.476 and the P has a value of up to 95.319 kW in operating conditions with a wind speed range between 1 m/s and 10 m/s. In addition, the ratios of power to blade surface area (P/S) and the ratios of power to blade volume (P/V) at the wind speed of 5 m/s were also investigated. The results show that rotors with blades ranging from 3 m to 5 m will give much higher P/S and P/V values than other blade configurations under these operating conditions. This emphasizes that these blade configurations will bring more economic benefit because they will consume less material and reduce production time while still ensuring the required capacity value. Finally, the 5 m blade rotor with a capacity of 2.750 kW at a rated wind speed of 5 m/s was proposed as the rotor suitable for individual household use. This design can help millions of Vietnamese households be proactive in their power source, thereby contributing to the significant reduction of CO2 emissions from coal-fired power plants.